Anode catalytic layer and preparation method thereof, fuel cell

CN117525443BActive Publication Date: 2026-10-30DONGFENG MOTOR GRP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311462802.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-06
Publication Date
2026-10-30
Estimated Expiration
2043-11-06

AI Technical Summary

Technical Problem

[0005]本申请实施例提供了一种阳极催化层及其制备方法、燃料电池,以解决阳极进气口处的抗反极催化剂在持续的反极过程中更容易发生结构的腐蚀的技术问题

Benefits of technology

[0021]本申请实施例提供的阳极催化层,通过设置催化剂纳米颗粒的粒径呈现依序降低的梯度分布的第一催化层至第N催化层,在保证所述阳极催化层的氧还原催化性能和抗反极催化性能较好的同时,也使得第一催化层耐水气冲刷,催化性能容易保持稳定,抗反极催化剂不容易发生结构腐蚀。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117525443B_ABST
    Figure CN117525443B_ABST
Patent Text Reader

Abstract

The application relates to an anode catalytic layer, which comprises a first catalytic layer to an Nth catalytic layer, N is an integer not less than two, the first catalytic layer to the Nth catalytic layer are sequentially distributed from one side to the other side of the anode catalytic layer, the first catalytic layer to the Nth catalytic layer all comprise Nafion, catalyst nanoparticles dispersed in the Nafion, the catalyst nanoparticles comprise oxygen reduction catalyst nanoparticles and anti-reverse catalyst nanoparticles, wherein the particle size of the catalyst nanoparticles in the first catalytic layer to the Nth catalytic layer presents a gradient distribution of sequentially decreasing. The application sets the first catalytic layer to the Nth catalytic layer with the particle size of the catalyst nanoparticles presenting a gradient distribution of sequentially decreasing, so that the oxygen reduction catalytic performance and the anti-reverse catalytic performance of the anode catalytic layer are ensured to be good, meanwhile, the first catalytic layer is resistant to water gas flushing, the catalytic performance is easy to keep stable, and the anti-reverse catalyst is not easy to be structurally corroded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of fuel cells, and more particularly to fuel cell catalyst layers. Background Technology

[0002] To address the increasing global energy consumption and environmental pollution caused by the use of fossil fuels, renewable and environmentally friendly energy solutions are constantly being developed. Hydrogen fuel cell vehicles and lithium-ion battery vehicles are two low-carbon transportation modes. Hydrogen fuel cell vehicles have certain advantages over lithium-ion battery vehicles due to their faster refueling and longer driving range per charge.

[0003] Currently, the mainstream hydrogen fuel cell is the proton exchange membrane fuel cell. During operation, hydrogen fuel "starvation" can occur due to dust blockage and low-temperature icing, leading to severe carbon corrosion at the anode and causing reverse polarity, significantly impacting the battery's lifespan. Currently, anti-reverse polarity catalysts such as ruthenium oxide and terephthalic acid oxide are often added to the anode to promote water electrolysis and prevent carbon corrosion. However, these anti-reverse polarity catalysts are very expensive (approximately five times the price of phosphorus), so improving their utilization rate and reducing their dosage is key to commercialization and cost reduction. Scientists are currently focusing on improving the anti-reverse polarity performance of batteries and reducing commercialization costs by searching for non-precious metal anti-reverse polarity catalysts at the material level and improving their dispersibility.

[0004] During the reverse polarity process of a proton exchange membrane fuel cell, the anti-reverse polarity catalyst at the anode inlet is more susceptible to structural corrosion due to the scouring effect of water vapor in the flow channel. This leads to the rapid loss of the anti-reverse polarity catalyst, which in turn exacerbates the carbon corrosion reaction and reduces the battery life. Summary of the Invention

[0005] This application provides an anode catalyst layer and its preparation method, as well as a fuel cell, to solve the technical problem that the anti-reverse catalyst at the anode inlet is more prone to structural corrosion during continuous reverse polarization.

[0006] In a first aspect, embodiments of this application provide an anode catalyst layer, the anode catalyst layer comprising a first catalyst layer to an Nth catalyst layer, where N is an integer not less than two, the first catalyst layer to the Nth catalyst layer being sequentially distributed from one side to the other side of the anode catalyst layer, each of the first catalyst layer to the Nth catalyst layer comprising Nafion and catalyst nanoparticles dispersed in the Nafion, the catalyst nanoparticles comprising oxygen reduction catalyst nanoparticles and anti-reverse polarization catalyst nanoparticles, wherein the particle size of the catalyst nanoparticles in the first catalyst layer to the Nth catalyst layer exhibits a gradient distribution that decreases sequentially.

[0007] In some embodiments of this application, the polydispersity index of the catalyst nanoparticles in the first to Nth catalyst layers is a value between 0.28 and 0.37.

[0008] In some embodiments of this application, the particle size of the catalyst nanoparticles in the first to Nth catalyst layers is between 200 and 500 nm.

[0009] In some embodiments of this application, N is five, the average particle size of the catalyst nanoparticles in the first catalyst layer is 460-500 nm, the average particle size of the catalyst nanoparticles in the second catalyst layer is 460-500 nm, the average particle size of the catalyst nanoparticles in the third catalyst layer is 380-420 nm, the average particle size of the catalyst nanoparticles in the fourth catalyst layer is 250-280 nm, and the average particle size of the catalyst nanoparticles in the fifth catalyst layer is 200-230 nm.

[0010] In some embodiments of this application, the oxygen reduction catalyst includes at least one of a Pt / C catalyst, a Pt alloy catalyst, a non-Pt-based noble metal catalyst, and a non-noble metal catalyst.

[0011] In some embodiments of this application, the anti-reverse polarity catalyst includes at least one of IrO2, RuO2, Ir alloy catalyst, and Ru alloy catalyst.

[0012] Secondly, embodiments of this application provide a method for preparing an anode catalyst layer, the method comprising the following steps:

[0013] It provides an oxygen reduction catalyst and an anti-reverse polarity catalyst, which are mixed with Nafion and isopropanol to form a mixture;

[0014] A first to an Nth sand mill are provided. The mixture is taken and added to the first to the Nth sand mill respectively and sand milled and dispersed to obtain a first to an Nth slurry respectively.

[0015] A support layer is provided, and the first to Nth slurries are sequentially disposed on the support layer along a predetermined direction parallel to the surface of the support layer. After removing the isopropanol, the first to Nth catalyst layers are formed respectively, thus forming the anode catalyst layer.

[0016] The grinding balls used in the first and Nth sand mills have particle sizes ranging from the first to the fifth particle size, respectively, with the first to the fifth particle sizes decreasing sequentially.

[0017] In some embodiments of this application, the first to Nth particle sizes are all between 0.1 and 3 mm.

[0018] In some embodiments of this application, N is five, and the first to fifth particle sizes are 3 mm, 0.6 mm, 0.3 mm, 0.2 mm, and 0.1 mm, respectively.

[0019] Thirdly, this application provides a fuel cell, which includes an anode module and a cathode module. The anode module includes an anode catalyst layer and an anode gas flow channel disposed on the anode catalyst. The distribution direction of the first to the Nth catalyst layers is the same as the overall flow direction of the gas flow in the anode gas flow channel.

[0020] The technical solutions provided in this application have the following advantages compared with the prior art:

[0021] The anode catalyst layer provided in this application embodiment has a gradient distribution of catalyst nanoparticles with sequentially decreasing particle size from the first catalyst layer to the Nth catalyst layer. This ensures good oxygen reduction catalytic performance and anti-reverse polarization catalytic performance of the anode catalyst layer, while also making the first catalyst layer resistant to water vapor erosion, its catalytic performance easy to maintain stability, and the anti-reverse polarization catalyst less prone to structural corrosion. Attached Figure Description

[0022] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0023] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1 This is a schematic diagram of the structure of the anode catalyst layer provided in the embodiments of this application;

[0025] Figure 2 This is a schematic diagram of the structure of a fuel cell provided in an embodiment of this application;

[0026] Figure 3 This is a pore size distribution diagram of the first to fifth catalyst layers in Example 1 of this application;

[0027] Figure 4 The graphs show the reverse polarization curves of Examples 1, 2, and the comparative example. Detailed Implementation

[0028] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0029] Unless otherwise specified, the terminology used herein should be understood as having the meaning as commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. In case of any conflict, this specification shall prevail.

[0030] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0031] Existing proton exchange membrane fuel cells have a technical problem: the anti-reverse catalyst at the anode inlet is more prone to structural corrosion during continuous reverse polarization.

[0032] The technical solution provided in this application is to solve the above-mentioned technical problems, and the general idea is as follows:

[0033] Firstly, this application provides an anode catalyst layer, please refer to... Figure 1 The anode catalyst layer includes a first catalyst layer 11 to an Nth catalyst layer, where N is an integer not less than two. The first catalyst layer 11 to the Nth catalyst layer are sequentially distributed from one side to the other side of the anode catalyst layer. Each of the first catalyst layer 11 to the Nth catalyst layer includes Nafion and catalyst nanoparticles dispersed in the Nafion. The catalyst nanoparticles include oxygen reduction catalyst nanoparticles and anti-reverse polarity catalyst nanoparticles. The particle size of the catalyst nanoparticles in the first catalyst layer 11 to the Nth catalyst layer exhibits a gradient distribution that decreases sequentially.

[0034] Nafion refers to a perfluorosulfonic acid-based polymer, a commercially available product. In proton exchange membrane fuel cells, it is typically present in solution form. The specific technical details of Nafion in this application are the same as those in known technologies.

[0035] Oxygen reduction catalysts are commonly used catalysts at the anode of proton exchange membrane fuel cells. This application may select specific types of oxygen reduction catalysts based on common knowledge in the field.

[0036] Anti-reverse catalysts are commonly used catalysts in proton exchange membrane fuel cells. This application can select specific types of anti-reverse catalysts based on common knowledge in the field.

[0037] The catalyst nanoparticles in the first catalyst layer 11 to the Nth catalyst layer exhibit a gradient distribution with progressively decreasing particle size. Larger catalyst nanoparticles are less susceptible to water vapor erosion. When the anode catalyst layer is applied in a proton exchange membrane fuel cell, the first catalyst layer 11, with its larger catalyst nanoparticle size, can be positioned near the anode inlet, while the Nth catalyst layer, with its smaller catalyst nanoparticle size, can be positioned away from the anode at the air outlet. The first catalyst layer 11's resistance to water vapor erosion helps maintain stable catalytic performance of the anode catalyst layer and reduces the likelihood of structural corrosion of the anti-reverse electrode catalyst. The increased specific surface area of ​​the catalyst nanoparticles after the particle size reduction results in better catalytic performance. The progressively decreasing particle size of the catalyst nanoparticles in the first catalyst layer 11 to the Nth catalyst layer helps ensure good oxygen reduction catalytic performance and anti-reverse electrode catalytic performance of the anode catalyst layer.

[0038] This application sets the first catalyst layer 11 to the Nth catalyst layer with a gradient distribution of catalyst nanoparticle size that decreases sequentially. This ensures good oxygen reduction catalytic performance and anti-reverse polarization catalytic performance of the anode catalyst layer, while also making the first catalyst layer 11 resistant to water vapor erosion, making it easy to maintain stable catalytic performance, and making the anti-reverse polarization catalyst less prone to structural corrosion.

[0039] In some embodiments of this application, the polydispersity index of the catalyst nanoparticles in the first catalyst layer 11 to the Nth catalyst layer is a value between 0.28 and 0.37.

[0040] The polydispersity index determines the uniformity of the catalyst nanoparticle size. In this application, the polydispersity index of the catalyst nanoparticles in the first catalyst layer 11 to the Nth catalyst layer is relatively small, the particle size distribution of the catalyst nanoparticles is relatively uniform, and the particle size gradient of the catalyst nanoparticles in the first catalyst layer 11 to the Nth catalyst layer is obvious, which can better adapt to the trend of the airflow intensity from the inlet to the outlet in the anode from strong to weak.

[0041] In some embodiments of this application, the particle size of the catalyst nanoparticles in the first catalyst layer 11 to the Nth catalyst layer is between 200 and 500 nm.

[0042] The particle size of the catalyst nanoparticles is between 200 and 500 nm. On the one hand, this ensures that the first catalyst layer 11 can withstand the water and gas scouring at the anode inlet. On the other hand, it ensures the overall catalytic activity and stability of the anode catalyst layer, as well as that the porosity of the anode catalyst layer structure is within a suitable range, thus ensuring water and gas transport efficiency.

[0043] In some embodiments of this application, N is five, the average particle size of the catalyst nanoparticles in the first catalyst layer 11 is 460-500 nm, the average particle size of the catalyst nanoparticles in the second catalyst layer 12 is 460-500 nm, the average particle size of the catalyst nanoparticles in the third catalyst layer 13 is 380-420 nm, the average particle size of the catalyst nanoparticles in the fourth catalyst layer 14 is 250-280 nm, and the average particle size of the catalyst nanoparticles in the fifth catalyst layer 15 is 200-230 nm.

[0044] The beneficial effects of the above particle size distribution are that the overall stability of the anode catalyst layer is better, and the first catalyst layer 11 to the fifth catalyst layer 15 are better adapted to the environment inside the anode where the airflow intensity changes from strong to weak from the inlet to the outlet. While minimizing the particle size and increasing the catalytic activity, it can withstand the water and gas scouring of different intensities inside the anode.

[0045] In some embodiments of this application, the oxygen reduction catalyst includes at least one of a Pt / C catalyst, a Pt alloy catalyst, a non-Pt-based noble metal catalyst, and a non-noble metal catalyst.

[0046] It is easy to understand that the above-mentioned oxygen reduction catalyst is a conventional catalyst in the field, and those skilled in the art can select specific catalyst products based on common knowledge.

[0047] In some embodiments of this application, the anti-reverse polarity catalyst includes at least one of IrO2, RuO2, Ir alloy catalyst, and Ru alloy catalyst.

[0048] It is easy to understand that the above-mentioned anti-reverse polarization catalysts are conventional catalysts in this field, and those skilled in the art can select specific catalyst products based on common knowledge.

[0049] Secondly, embodiments of this application provide a method for preparing an anode catalyst layer, the method comprising the following steps:

[0050] S1: Provides oxygen reduction catalyst and anti-reverse polarity catalyst, which is mixed with Nafion and isopropanol to form a mixture;

[0051] S2: Provide a first sand mill to a Nth sand mill, and take the mixture into the first sand mill to a Nth sand mill respectively and perform sand milling and dispersion to obtain a first slurry to a Nth slurry respectively;

[0052] S3: Provide a support layer by sequentially placing the first slurry to the Nth slurry onto the support layer along a predetermined direction parallel to the surface of the support layer. After removing the isopropanol, the first catalyst layer 11 to the Nth catalyst layer are formed, thus forming the anode catalyst layer.

[0053] The grinding balls used in the first and Nth sand mills have particle sizes ranging from the first to the fifth particle size, respectively, with the first to the fifth particle sizes decreasing sequentially.

[0054] Step S1 is a conventional method in the art, and the parameters such as the amount, concentration, and temperature of the oxygen reduction catalyst, anti-reverse polarization catalyst, Nafion, and isopropanol can be implemented in accordance with known techniques in the art.

[0055] It is readily understood that the support layer refers to the surface used to support the formation of the anode catalyst layer. In the art, the support layer generally refers to a proton exchange membrane or a gas diffusion layer. Both proton exchange membranes and gas diffusion layers are conventional structures in proton exchange membrane fuel cells.

[0056] Those skilled in the art can apply the first to the Nth slurry onto the support layer in a manner known in the art; for example, it can be done by spraying.

[0057] The method for preparing the anode catalyst layer can prepare the anode catalyst layer described in any embodiment of the first aspect. Therefore, the method for preparing the anode catalyst layer has at least all the beneficial effects brought about by the technical solution of the first aspect embodiment, which will not be elaborated here.

[0058] In some embodiments of this application, the first to Nth particle sizes are all between 0.1 and 3 mm.

[0059] It is easy to understand that the particle size of the grinding balls is selected between 0.1 and 3 mm, which can control the particle size of the catalyst nanoparticles within the range of 200 to 500 nm.

[0060] In some embodiments of this application, N is five, and the first to fifth particle sizes are 3 mm, 0.6 mm, 0.3 mm, 0.2 mm, and 0.1 mm, respectively.

[0061] It is easy to understand that the first to fifth particle sizes are 3 mm, 0.6 mm, 0.3 mm, 0.2 mm, and 0.1 mm, respectively. The particle sizes of the catalyst nanoparticles in the first to fifth catalyst layers 15 can be controlled within the ranges of 460–500 nm, 460–500 nm, 380–420 nm, 250–280 nm, and 200–230 nm, respectively.

[0062] In some embodiments of this application, the dispersion speed of the sand mill is 500-1500 r / min.

[0063] In some embodiments of this application, the duration of the sand milling dispersion is 10-20 minutes.

[0064] It is easy to understand that the dispersion speed of the sand mill and the particle size of the sand mill balls can be adjusted within a small range to control the particle size of the catalyst layer nanoparticles.

[0065] Thirdly, this application provides a fuel cell, please refer to... Figure 2 The fuel cell includes an anode module and a cathode module. The anode module includes an anode catalyst layer and an anode gas flow channel disposed on the anode catalyst. The distribution direction of the first catalyst layer 11 to the Nth catalyst layer is the same as the overall flow direction of the gas flow in the anode gas flow channel.

[0066] The anode airflow channel is a conventional structure in the art, and those skilled in the art can implement the anode airflow channel based on common knowledge.

[0067] As is easily understood, the fuel cell mentioned generally refers to a proton exchange membrane fuel cell.

[0068] To further illustrate the technical solution of this application, a specific example is also provided. Please refer to it. Figure 2 The fuel cell includes:

[0069] Proton exchange membrane 2;

[0070] An anode module is disposed on one side of the proton exchange membrane 2. The anode module includes an anode catalyst layer, a first gas diffusion layer 3, and an anode gas channel 4. The anode catalyst layer is disposed on the side of the anode module close to the proton exchange membrane 2. The anode gas channel 4 is disposed on the first gas diffusion layer 3 and includes an inlet 41 and an outlet 42.

[0071] A cathode module is disposed on the other side of the proton exchange membrane 2. The cathode module includes a cathode catalytic layer 5, a second gas diffusion layer 6, and a cathode gas flow channel 7. The cathode catalytic layer 5 is disposed on the side of the cathode module close to the proton exchange membrane 2, and the cathode gas flow channel 7 is disposed on the second gas diffusion layer 6.

[0072] It is easy to understand that the fuel cell described in the third aspect of this application is based on the anode catalyst layer described in the first aspect. The specific implementation of the fuel cell can be referred to the embodiments of the first aspect and common knowledge in the field of fuel cells. Since the fuel cell adopts some or all of the technical solutions of the embodiments of the first aspect, it has at least all the beneficial effects brought about by the technical solutions of the embodiments of the first aspect, which will not be repeated here.

[0073] The present application is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the application. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national standards. If there is no corresponding national standard, then general international standards, conventional conditions, or conditions recommended by the manufacturer are followed.

[0074] Example 1

[0075] This embodiment provides an anode catalyst layer and its preparation method, the method comprising the following steps:

[0076] Step (1): Weigh 1.79g of TKK 47% Pt / C, add 11.54g of water to wet the catalyst, add 57g of isopropanol and mechanically stir to mix, add 0.17g of IrO2 and 14.68g of Nafion solution, and then disperse for 20min at 1000r / min using a 3mm milling ball to obtain the first slurry;

[0077] Step (2): Take four portions of the same mixture and disperse them for 20 minutes at a speed of 800 r / min using 0.6 mm, 0.3 mm, 0.2 mm and 0.1 mm grinding balls respectively to obtain the second to fifth slurries with the same particle size.

[0078] Step (3): Add the obtained first to fifth slurries into different spray coating cylinders, take a 72×72mm proton exchange membrane, and spray it on a heating table at 80°C using the spraying method. Spray the first to fifth catalyst layers along the direction from one side of the proton exchange membrane to the other side to obtain the anode catalyst layer.

[0079] Example 2

[0080] This embodiment provides an anode catalyst layer and its preparation method, the method comprising the following steps:

[0081] Step (1): Weigh 1.79g of TKK 47% Pt / C, add 12.82g of water to wet the catalyst, add 58g of isopropanol and mechanically stir to mix, add 0.18g of IrO2 and 11.9g of Nafion solution, and then disperse for 20min at 1200r / min using 2mm sand milling balls to obtain the first slurry;

[0082] Step (2): Take four portions of the same mixture and disperse them for 20 minutes at a speed of 800 r / min using 0.8 mm, 0.3 mm, 0.2 mm and 0.1 mm grinding balls respectively to obtain the second to fifth slurries with the same particle size.

[0083] Step (3): Add the obtained first to fifth slurries into different spray coating cylinders, take a 72×72mm proton exchange membrane, and spray it on a heating table at 80°C using the spraying method. Spray the first to fifth catalyst layers along the direction from one side of the proton exchange membrane to the other side to obtain the anode catalyst layer.

[0084] Example 3

[0085] This embodiment provides an anode catalyst layer and its preparation method, the method comprising the following steps:

[0086] Step (1): Weigh 1.79g of TKK 47% Pt / C, add 12.82g of water to wet the catalyst, add 58g of isopropanol and mechanically stir to mix, add 0.18g of IrO2 and 11.9g of Nafion solution, and then disperse for 20min at 1200r / min using a 3mm milling ball to obtain the first slurry;

[0087] Step (2): Take four portions of the same mixture and disperse them for 20 minutes at a speed of 800 r / min using 1 mm, 0.7 mm, 0.4 mm and 0.2 mm grinding balls respectively to obtain the second to fifth slurries with the same particle size.

[0088] Step (3): Add the obtained first to fifth slurries into different spray coating cylinders, take a 72×72mm proton exchange membrane, and spray it on a heating table at 80°C using the spraying method. Spray the first to fifth catalyst layers along the direction from one side of the proton exchange membrane to the other side to obtain the anode catalyst layer.

[0089] Comparative Example

[0090] The only difference between this comparative example and Example 1 is that this comparative example uses 0.6mm grinding balls. Specifically:

[0091] This comparative example provides an anode catalyst layer and its preparation method, the method comprising the following steps:

[0092] Step (1): Weigh 1.79g of TKK 47% Pt / C, add 12.82g of water to wet the catalyst, add 58g of isopropanol and mechanically stir to mix, add 0.18g of IrO2 and 11.9g of Nafion solution, and then disperse for 20min at 1200r / min using a 6mm milling ball to obtain the anode catalyst slurry;

[0093] Step (2): Add the obtained anode catalyst slurry into the spray gun, take a 72×72mm proton exchange membrane, and spray it on a heating table at 80℃ using the spraying method to form the anode catalyst layer by spraying from one side of the proton exchange membrane to the other side.

[0094] Relevant experimental and effect data:

[0095] Nanoparticle size analysis was performed on the first to fifth slurries in Example 1 to test their particle size distribution. The results are shown in Table 1.

[0096] Gradient Particle Size 1 483 0.361 Gradient particle size 2 402 0.289 Gradient particle size 3 326 0.342 Gradient particle size 4 259 0.298 Gradient particle size 5 225 0.301

[0097] Table 1

[0098] The test results show that by changing the size of the grinding balls, the particle size of the slurry can be gradient controlled, with the particle size of the first to fifth slurries decreasing from 483nm to 225nm.

[0099] Mercury porosimetry was performed on the first to fifth catalyst layers obtained in Example 1 to test their pore size distribution. The test results are available for reference. Figure 3 . Figure 3 This is a pore size distribution diagram of the first to fifth catalyst layers in Example 1 of this application.

[0100] The pore size analysis results show that the pore size of the catalyst layer decreases continuously from the inlet to the outlet, indicating that a gradient particle size and pore size catalyst layer has been prepared.

[0101] The anode catalyst layers from Examples 1, 2, and the comparative example were prepared into corresponding 25cm diaphragms in the same manner. 2 The membrane electrode was subjected to a reverse polarity test after battery activation, maintaining 100% humidity, no back pressure, and operating at 65℃-200mA / cm. 2 The reverse polarity was then applied with a cutoff voltage of 1.5V, and the duration of the reverse polarity was measured. The results are as follows: Figure 4 As shown. Figure 4 The reverse polarization curves of Example 1, Example 2, and the comparative example are shown.

[0102] Depend on Figure 4 It is easy to see that in Examples 1 and 2 with gradient design, the anti-reverse polarization time reached 93 min and 106 min respectively. In contrast, the anti-reverse polarization time in Comparative Example 1 was 66 min, indicating that the catalyst layer with gradient particle size has a significant improvement in anti-reverse polarization performance.

[0103] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the referred range.

[0104] In this application, unless otherwise stated, directional terms such as "upper" and "lower" specifically refer to the drawing directions in the accompanying drawings. Furthermore, in the description of this application, the terms "comprising," "including," etc., mean "including but not limited to." Moreover, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element. In this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this document, "and / or" describes the relationship between related objects, indicating that three relationships can exist; for example, A and / or B can represent: A alone, A and B simultaneously, or B alone. For associations involving three or more related objects described using "and / or", it indicates that any one of the three related objects can exist alone, or at least two of them can exist simultaneously. For example, for A, and / or B, and / or C, it can mean that any one of A, B, and C exists alone, or any two of them exist simultaneously, or all three of them exist simultaneously. In this document, "at least one" means one or more, and "more than one" means two or more. "At least one", "at least one of the following", or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can each be single or multiple.

[0105] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.

Claims

1. An anode catalyst layer, characterized in that, The anode catalyst layer includes a first catalyst layer to a fifth catalyst layer, which are sequentially distributed from the anode inlet side to the anode outlet side. Each of the first to fifth catalyst layers includes Nafion and catalyst nanoparticles dispersed in the Nafion. The catalyst nanoparticles include oxygen reduction catalyst nanoparticles and anti-reverse polarity catalyst nanoparticles. The average particle size of the catalyst nanoparticles in the first catalyst layer is 460-500 nm, the average particle size of the catalyst nanoparticles in the second catalyst layer is 460-500 nm, the average particle size of the catalyst nanoparticles in the third catalyst layer is 380-420 nm, the average particle size of the catalyst nanoparticles in the fourth catalyst layer is 250-280 nm, and the average particle size of the catalyst nanoparticles in the fifth catalyst layer is 200-230 nm.

2. The anode catalyst layer according to claim 1, characterized in that, The polydispersity index of the catalyst nanoparticles in the first to fifth catalyst layers is between 0.28 and 0.

37.

3. The anode catalyst layer according to claim 1, characterized in that, The oxygen reduction catalyst includes at least one of Pt / C catalyst, Pt alloy catalyst, non-Pt-based noble metal catalyst, and non-noble metal catalyst.

4. The anode catalyst layer according to claim 1, characterized in that, The anti-reverse polarization catalyst includes at least one of IrO2, RuO2, Ir alloy catalyst, and Ru alloy catalyst.

5. A method for preparing the anode catalyst layer according to any one of claims 1-4, characterized in that, The method includes the following steps: It provides an oxygen reduction catalyst and an anti-reverse polarity catalyst, which are mixed with Nafion and isopropanol to form a mixture; A first to a fifth sand mill are provided. The mixture is added to the first to the fifth sand mill respectively and sand milled and dispersed to obtain the first to the fifth slurry respectively. A support layer is provided, and the first to fifth slurries are sequentially disposed on the support layer along a predetermined direction parallel to the surface of the support layer. After the isopropanol is removed, the first to fifth catalyst layers are formed respectively, thus forming the anode catalyst layer. The particle size of the grinding balls used in the first to fifth sand mills are respectively the first particle size to the fifth particle size, with the first particle size to the fifth particle size decreasing in sequence.

6. The method for preparing the anode catalyst layer according to claim 5, characterized in that, The first to fifth particle sizes are all between 0.1 and 3 mm.

7. The method for preparing the anode catalyst layer according to claim 6, characterized in that, The first to fifth particle sizes are 3 mm, 0.6 mm, 0.3 mm, 0.2 mm, and 0.1 mm, respectively.

8. A fuel cell, characterized in that, The fuel cell includes an anode module and a cathode module. The anode module includes an anode catalyst layer as described in any one of claims 1-4 and an anode gas flow channel disposed on the anode catalyst layer. The distribution direction of the first to fifth catalyst layers is the same as the overall flow direction of the gas flow in the anode gas flow channel.

Citation Information

Patent Citations

  • Membrane electrode catalyst layer with gradient pore structure as well as preparation method and application of membrane electrode catalyst layer

    CN114122413A

  • Anti-antipolar CCM of fuel cell, preparation method of anti-antipolar CCM and fuel cell

    CN116864700A